Are PSP patients included in clinical trials representative of the general PSP population?. (September 2019) - Mariani, Louise-Laure; Guimarães-Costa, Raquel; Grabli, David; Le Toullec, Benjamin; Cormier-Dequaire, Florence; Degos, Bertrand; Dubois, Bruno; Vidailhet, Marie; Lacomblez, Lucette; Corvol, Jean-Christophe
Abstract: Background: Progressive supranuclear palsy (PSP) is a rare parkinsonian syndrome with a wide spectrum of clinical presentations. Recently, the MDS published revised diagnosis criteria to provide early and reliable diagnosis of PSP and its variants. Two large randomized clinical trials were initiated in 2017, but the question remains regarding the extrapolation of their results to the general PSP population. Objective: To determine if PSP patients included in clinical trials are representative of the general PSP population. Methods: We conducted a single center retrospective study of PSP patients referred to a tertiary department of Neurology (Pitié-Salpêtrière Hospital, Paris) for clinical diagnosis and clinical trial inclusion, over a 12-month period. We collected and analyzed gender, age at examination, age at disease onset, disease duration, and core clinical features regarding oculo-motor dysfunction, postural instability, akinesia and cognitive dysfunction, and inclusion/exclusion criteria of clinical trials to assess eligibility for inclusion. We assessed the relative proportions of different PSP subtypes, as defined by the MDS-PSP criteria, in the whole population compared to patients eligible in trials. Results: 206 PSP patients were included, among which 175 (85%) were diagnosed with probable PSP-Richardson's syndrome (RS) subtype, with a mean age of 73 and mean disease duration of 5 years. Among those patients, 29 (21%) were eligible (age 71 ± 10.7, disease duration 3.1 ± 1.2 years) and 19 were included in trials, all with a diagnosis of probable PSP-RS. As compared to the whole population, patients included in clinical trials tended to be younger, and showed more PSP-RS subtypes (p < 0.05). Conclusion: The PSP population included in trials is very similar to the general PSP population, but younger, with shorter disease duration. By definition, only probable PSP subtypes are included in clinical trials. The time window for inclusion is short because of diagnosis delay, fast disease progression and old age of the population. Highlights: Current ongoing clinical trials in PSP are done on the PSP-RS subtype. However, many clinical presentations of PSP exist, defined in the recent MDS criteria. We assessed if PSP patients in clinical trials are representative of the general PSP population. The trial population is very similar, although PSP-P and PSP-PGF are not represented. Generalizability of clinical trials results is crucial to define the target population.